When Truth Commission Models Travel: Explaining the Norwegian Case - Skaar; Elin (International Journal of Transitional Justice, 2023)
This article explores ‘late justice’ in the context of settler democracies with a history of racism, using Norway as a case study. It examines the background for the Norwegian Truth and Reconciliation Commission (TRC), established by the Norwegian Parliament in 2018 to investigate the consequences of historical and ongoing assimilation of the indigenous Sami people and two national minorities. I argue that although the Norwegian TRC was established in direct response to an initiative from the Sami Parliament, its successful creation was a result of political negotiations involving a series of actors, including Sami activists, mainstream politicians and various interest organizations. The protagonists pushing for a truth commission were in turn encouraged and inspired by a global focus on transitional justice, truth commissions and indigenous rights. Based on a desk study, interviews and media reports, and applying a theoretical framework emphasizing agency and norm diffusion, I argue that while the Norwegian TRC has explicitly used truth commissions elsewhere in the world – particularly the Canadian TRC – as models, it is quite unique in terms of mandate and design.